The Influence of Visionary Leadership Style on Organizational Commitment of Private University Lecturers - Basri Basri; Rosmala Dewi; Saud Purba (AL-ISHLAH: Jurnal Pendidikan, 2021)
Good leadership is one of the virtues that need to exist in an organization. In carrying out the roles, duties, and responsibilities, every leader has their leadership style. This study aims to investigate the effect of visionary leadership style on organizational commitment. The study used quantitative methods with ex post facto research. The investigation begins after the facts have already occurred, and the researchers do not control nor manipulate the variables studied. The population in this study consisted of 294 lecturers, with a sample size of 169 people. The instrument used in this research was a questionnaire. The data analysis utilized was simple linear regression analysis processed by the SPSS. Findings show that the variable visionary leadership style (X) positively influences the variable organizational commitment of private university lecturers in Banda Aceh City. The results obtained are tcount ttable or 8.741 1.974. In addition, there is a strong relationship or correlation between variables X and Y of 56% and the coefficient of determination (RSquare) of .314, indicating that there is an influence of the independent variable (visionary leadership style) on the dependent variable (organizational commitment) of 31.4%.